Camel hump oil and milk vs. plant-based oils in aging-related oxidative stress and inflammation: a systematic review and meta-analysis - Alzunaidy, Nada A. (Frontiers in Nutrition, 2026)
BackgroundCamel hump oil (CHO) is high in unsaturated fatty acids, tocopherols, and bioactive lipids, and it has long been used in Arabian medicine. While camel milk has been extensively studied for its antioxidant and anti-inflammatory properties, direct information on CHO anti-aging is limited. This study aimed to conduct a comprehensive review and meta-analysis of the effects of CHO and camel milk derivative products on age-related oxidative stress and inflammation compared with plant oils.MethodsWe followed the Preferred Reporting Items for Systematic reviews and Meta-Analysis (PRISMA) 2020 guidelines. An extensive search was conducted across PubMed, Scopus, Web of Science, and the Cochrane Library databases to identify relevant publications up to August 2025. We included cell, animal, and human research that evaluated therapies using CHO, camel milk (as a surrogate), or comparable plant oils (olive, camelina, and coconut). The primary outcomes were indicators of oxidative stress [superoxide dismutase (SOD) and malondialdehyde (MDA)] and inflammation. Random-effects meta-analyses were carried out.ResultsOf 612 data points, 11 investigations were included (2 direct CHO studies, 4 camel milk studies, and 5 plant oil studies). In animal studies, CHO improved the lipid profile and provided photoprotection against ultraviolet (UV) damage. A pooled examination of surrogate and comparative evidence revealed that therapies containing camel-derived and plant oils significantly increased SOD activity (SMD + 1.42, 95% CI: 0.85–1.99) and decreased MDA levels (SMD −1.28, 95% CI: −1.80 to −0.76). A significant constraint is the reliance on camel milk as a substitute for CHO, which presents indirectness due to changes in bioactive chemical profiles. The risk of bias was moderate.ConclusionPreclinical research suggests that camel-derived products, especially CHO, influence important aging biomarkers through antioxidant and anti-inflammatory pathways, with effect levels equivalent to or greater than those of some plant oils. However, the available research is mostly preclinical. Well-designed human clinical trials are required to test efficacy, determine dose, and confirm the translational potential of CHO in an anti-aging diet.Systematic review registrationRegistered with PROSPERO 2025 CRD420251162233. It is available at https://www.crd.york.ac.uk/PROSPERO/view/CRD420251162233.